The Relationship between Social Support and Well-Being in Elementary School in Singkawang - Junita, Junita; Suwanto, Insan; Setyowati, Rini (Universitas PGRI Semarang, 2024)
The objectives of this study are: 1) to describe the level of social support in students at SD Negeri 15 Singkawang, 2) to describe the level of well-being in students at SD Negeri 15 Singkawang, 3) to examine the relationship between social support and well-being in students at SD Negeri 15 Singkawang. This type of research is quantitative correlation design. The population of this study were all students in grades V and VI of SD Negeri 15 Singkawang, totaling 76 students. The population was sampled using saturated sampling technique, the sample used was 76 students. Data collection techniques in this study with questionnaire and scale research instruments. The Social Support Questionnaire amounted to 37 statements, the validity value was in the range of 0.329-0.881 while the reliability value Î± was 0.945 and the Well-being Scale amounted to 26 statements, the validity value was in the range of 0.305-0.801 while the reliability value Î± was 0.903 with yes and no answer options. The data analysis techniques used are percentage and correlation. The results showed that the level of student social support was in the low category (57.15%), meaning that students did not get optimal social support from those closest to them while following the learning process at school. The results of the level of well-being of students are in the low category (59.41%), meaning that students have not fully felt happiness or well-being.